PENGARUH APLIKASI POC ECO-ENZYME TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELEDRI (Apium graveolens L.) PADA TANAH ULTISOL - Fadilah S, Oktaviani; Wartono; Sumini, Sumini (Universitas Muhammadiyah Bengkulu, 2024)
This research aimed to determine the effect of POC eco-enzyme application on the growth and production of celery plants in ultisol soil. This research was carried out in Rahmah Village, South Lubuklinggau District 1, Lubuklinggau City from April to June 2024. This research used an experimental design method with a randomized block design prepared by non-factorial, consisting of six treatment levels with 4 replications. The treatments tried in this research were the following concentrations of liquid organic fertilizer eco-enzyme: E0: No POC Eco-enzyme treatment (control), E1: POC Eco-enzyme concentration 1.00ml/liter, E2: POC Eco-enzyme concentration 1.25ml/liter, E3: POC Eco-enzyme concentration 1.50ml/liter, E4: POC Eco-enzyme concentration 1.75ml/liter, and E5: POC Eco-enzyme concentration 2.00ml/liter. The results of the research showed that the application of POC eco-enzyme to the growth and production of celery plants had a real to very significant effect on all the variables observed and in the E4 treatment, namely the application of eco-enzyme with a concentration of 1.75 ml/liter showed the best results on growth and production. celery plants in ultisol soil. Keywords: Ecoenzyme, Growth Hormone, Organic Fertilizer